Motivation : the ultimate guide to leading your team - Stothart, Catherine (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Motivation is regarded as a cornerstone of performance in the workplace, both personally and for organisations. If you are a leader, manager or HR professional, this book will show you how to tap into what motivates every individual so that you can enable them to use their talents and fulfil their potential. You will also learn more about your own motivation and how this impacts your leadership style. Written by bestselling author and leadership coach, Catherine Stothart, the book captures the essence of motivation in an insightful and practical way. You will learn specific tools and techniques for four key management capabilities - how to engage, develop, delegate to, and communicate with, your teams. You will also find out how to sustain your own motivation and be resilient through setbacks. Using activities, case studies, models, tools, tips, and templates for practical action, this book is ideal for those who want to know how to motivate their teams, improve their wellbeing, and feel motivated themselves. It is also invaluable to HR managers, executive and life coaches and learning and development professionals"--
Keywords: Employee motivation; Leadership; Management; Teams in the workplace; BUSINESS & ECONOMICS / Motivational; BUSINESS & ECONOMICS / Human Resources & Personnel Management